2016
DOI: 10.1155/2016/9850457
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of DWDM Demultiplexer Using Regression Analysis

Abstract: We propose a novel twelve-channel Dense Wavelength Division Multiplexing (DWDM) demultiplexer, using the two-dimensional photonic crystal (2D PC) with square resonant cavity (SRC) of ITU-T G.694.1 standard. The DWDM demultiplexer consists of an input waveguide, SRC, and output waveguide. The SRC in the proposed demultiplexer consists of square resonator and microcavity. The microcavity center rod radius (Rm) is proportional to refractive index. The refractive index property of the rods filters the wavelengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the 2D PC is a better choice for designing optical devices due to many advantages such as nano size, complete PBG and better light manipulation to integrate in PIC. The 2D PC design with diverse components like LASER (Meier et al1999), filter (Fan et al1998), sensor (Fenzl et al2014), demultiplexer (Balaji et al 2016), logic gates (Zhang et al 2007), encoder (Mehdizadeh et al2017), Micro ring resonator (Ali Shahidinejad et al 2018), Add Drop filter (Joannopoulos et al1997;Hsiao et al2009;Mahmoud et al2012;Rajasekar et al2018;Sathyadevaki et al2017;Qiang, et al2004;Alipour-Banaei et al2014;Robinson et al2018;Rezaee et al2018;Rashki et a.2017;Chhipa et al2016, Alipour-Banaei et al2014Massoudi et al2019) and etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 2D PC is a better choice for designing optical devices due to many advantages such as nano size, complete PBG and better light manipulation to integrate in PIC. The 2D PC design with diverse components like LASER (Meier et al1999), filter (Fan et al1998), sensor (Fenzl et al2014), demultiplexer (Balaji et al 2016), logic gates (Zhang et al 2007), encoder (Mehdizadeh et al2017), Micro ring resonator (Ali Shahidinejad et al 2018), Add Drop filter (Joannopoulos et al1997;Hsiao et al2009;Mahmoud et al2012;Rajasekar et al2018;Sathyadevaki et al2017;Qiang, et al2004;Alipour-Banaei et al2014;Robinson et al2018;Rezaee et al2018;Rashki et a.2017;Chhipa et al2016, Alipour-Banaei et al2014Massoudi et al2019) and etc.…”
Section: Introductionmentioning
confidence: 99%
“…In last decades it has been shown that photonic crystals (PhCs) [1,2] which consist of regular arrangement of dielectric materials with periodic refractive indices can be very useful for designing different kinds of optical devices [3][4][5]. The realization of optical filters [6][7][8][9][10], demultiplexers [11][12][13][14][15][16], logic gates [17][18][19][20][21][22], coders [23][24][25][26][27][28][29], adders [30][31][32][33][34][35] and analog to digital converters [36][37][38][39][40] proves the ability of photonic crystals for playing a crucial role in the next generation of all optical networks. An all optical phase shift keying (PSK) demodulator was designed using 2D PhCs [41].…”
Section: Introductionmentioning
confidence: 99%
“…The design is reported with higher transmission efficiency up to 90% [35]. Following that, a 12-channel DWDM demultiplexer was designed using central defect (Rm) with a high Q-factor of 7890, transmission efficiency, uniform spectral linewidth, and uniform channel spacing of about 0.2 nm, −42 dB [36]. From the literature survey, it has been studied that optical demultiplexers are designed using different shapes and resonant cavities with different lattices, and are reported to have high transmission efficiency, Q-factor and minimal crosstalk.…”
Section: Introductionmentioning
confidence: 99%